Development of web-based gis for special education school in Johor Bahru district - Nurulhirda Johari, 1995-, author 613488 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2018